2003
DOI: 10.1046/j.1471-4159.2003.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretoneurin promotes pertussis toxin‐sensitive neurite outgrowth in cerebellar granule cells

Abstract: The neuropeptide secretoneurin (SN) is an endoproteolytic product of the chromogranin secretogranin II. We investigated the effects of SN on the differentiation of immature cerebellar granule cells derived from the external granular layer (EGL). Secretoneurin caused concentration-dependent increases in neurite outgrowth, reflecting differentiation. The maximum effect was reached at a concentration of 100 nM SN. Secretoneurin immunoneutralization using specific antiserum significantly decreased neurite outgrowt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…31 This is in contrast to our findings on ECs and to the observations made with VEGF on neuronal cells. 24 Presently, we can only speculate what mechanisms cause these differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…31 This is in contrast to our findings on ECs and to the observations made with VEGF on neuronal cells. 24 Presently, we can only speculate what mechanisms cause these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…24 Presently, we can only speculate what mechanisms cause these differences. One possible explanation would be the use of different neuronal cells in these studies (superior cervical ganglia and dorsal root ganglion cells 24 versus granular cells of the cerebellum 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01 vs. control. In agreement with previous studies, we found SN to have functions similar to those of glial cell-derived neurotrophic factor (GDNF), correlated to growth (18,(22)(23)(24) and repair (6,25,26) of injured neural tissue. Some literature has indicated that expression of SN is upregulated after cerebral ischemic insult (7).…”
Section: Discussionsupporting
confidence: 92%
“…In several recent reports, chromogranin/SN proteins have been found to be closely correlated with synaptic disturbance caused by neuronal/ glial and inflammatory mechanisms in conditions such as Alzheimer disease (3)(4)(5). It has also been reported that SN can promote the neurite outgrowth of immature cerebellar granule cells (6). Furthermore, in a recent report, increased expression of SN was found in an animal model after transient forebrain ischemia (7).…”
Section: Introductionmentioning
confidence: 99%
“…study of freshly sorted adult human NG2 glia [125] Neurotransmission [171,172] Chromogranin C, Chgc Gene expr. study of freshly sorted adult human NG2 glia [125] Neurite outgrowth [173] and angiogenesis [174].…”
Section: Neuregulinsmentioning
confidence: 99%